PENGARUH FIRM SIZE, INTANGIBLE ASSET DAN TAX MINIMIZATION TERHADAP TRANSFER PRICING - Leonita Mutiara Bintang; desi jelanti (Jurnal Nusa Akuntansi, 2026)
This study aims to determine the effect of Firm Size, Intangible Assets, and Tax Minimization on Transfer Pricing. This type of research uses quantitative. The population used in this study was 90 energy sector companies. The sampling technique used purposive sampling technique, which determines the criteria that are most suitable for this research. So the sample used in this study was 8 companies with a research period of 5 years so that the data processed was 40 data. This study uses panel data regression analysis techniques. The results of the study simultaneously show that Firm Size, Intangible Assets, and Tax Minimization have a simultaneous effect on Transfer Pricing. Partially, Firm Size and Intangible Assets do not affect Transfer Pricing, while Tax Minimization affects Transfer Pricing.